(untitled) (The International Journal for Scientific Research, 2024)
This study seeks to explore the impact of social media on employee performance in companies in Riyadh, Saudi Arabia. The research aims to analyze how social media use affects employee productivity, communication quality, and job satisfaction. The research was conducted using a comprehensive questionnaire distributed to 300 employees from various sectors, including education, engineering, and management. The study relied on statistical analysis methods to analyze the collected data, including analysis of variance and regression. The results showed that there is a complex relationship between social media use and employee performance. On the one hand, the data indicated that social media can enhance the quality of communication between employees, which contributes to improving collaboration and innovation in work teams. On the other hand, it was noted that excessive use of social platforms may lead to a decrease in productivity and an increase in distraction. The study concluded that organizations need to adopt effective strategies to manage the use of social media in the workplace. It is recommended to develop clear policies that address the optimal use of these platforms and achieve a balance between benefiting from their advantages and reducing their negative effects. This study enhances the understanding of the impact of social media on work environments and provides practical recommendations to improve job performance in companies.